2014
DOI: 10.1088/0004-637x/784/2/165
|View full text |Cite
|
Sign up to set email alerts
|

A Solar Eruption Driven by Rapid Sunspot Rotation

Abstract: We present the observation of a major solar eruption that is associated with fast sunspot rotation. The event includes a sigmoidal filament eruption, a coronal mass ejection, and a GOES X2.1 flare from NOAA active region 11283. The filament and some overlying arcades were partially rooted in a sunspot. The sunspot rotated at ∼10 • per hour rate during a period of 6 hours prior to the eruption. In this period, the filament was found to rise gradually along with the sunspot rotation. Based on the HMI observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…On the one hand, we did not observe any significant emergence of magnetic field during the period of recurrent flare occurrence, while on the other hand, we detected a peculiar horizontal velocity pattern during our observation time interval. As did Ruan et al (2014), before the X2.1 class flare we noted a clockwise rotation of the main negative sunspot, but we also found a persistent shear motion of the positive and negative polarities along the PIL. However, from the Poynting fluxes computed from the emergence of the magnetic flux and from the shearing of magnetic field lines due to tangential motions on the surface, we found that, even if the energy flux coming from the shearing motions seems to be the main source of energy in the corona during our observation time interval, this energy is lower than the energy released by the M and X flares.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…On the one hand, we did not observe any significant emergence of magnetic field during the period of recurrent flare occurrence, while on the other hand, we detected a peculiar horizontal velocity pattern during our observation time interval. As did Ruan et al (2014), before the X2.1 class flare we noted a clockwise rotation of the main negative sunspot, but we also found a persistent shear motion of the positive and negative polarities along the PIL. However, from the Poynting fluxes computed from the emergence of the magnetic flux and from the shearing of magnetic field lines due to tangential motions on the surface, we found that, even if the energy flux coming from the shearing motions seems to be the main source of energy in the corona during our observation time interval, this energy is lower than the energy released by the M and X flares.…”
Section: Discussionsupporting
confidence: 81%
“…5d) their longitudes differ by about 15 . Moreover, in the same maps it is also possible to recognize the clockwise rotation of the positive spot, already interpreted by Ruan et al (2014) as the main mechanism able to transport a considerable amount of magnetic energy into the corona before the X2.1 flare occurred on September 6.…”
Section: Horizontal Velocity Fieldsmentioning
confidence: 72%
See 1 more Smart Citation
“…In Ruan et al (2014), a study focusing on the 6-hr long pre-flare sunspot activity and photospheric magnetic field evolution of the X2.1 event from AR 11283 was presented. It was concluded that the persistent sunspot rotation plays an important role in twisting, energizing, and destabilizing the coronal filament-flux rope system.…”
Section: Introductionmentioning
confidence: 99%
“…The X1.8 flare on 2011 September 7 is notable because of a substantial amount of chromospheric material being ejected. The field evolution around the time of the two X-class flares was described by Ruan et al (2014Ruan et al ( , 2015. These studies note that both major flares were associated with clear sunspot rotation.…”
Section: Ar 11283mentioning
confidence: 90%